ANALISIS KUALITAS PRODUK DAN STRATEGI PEMASARAN SARANG BURUNG WALET DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Whila, Adelina; Munawaroh, RR Siti (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This study aims to determine the quality of the product, in this case the quality of swallow nests, as well as to analyze the marketing strategy of swallow nests in Pelaihari District, Tanah Laut Regency. Moreover, the data were collected by conducting interviews with swallow nest entrepreneurs in Pelaihari District, Tanah Laut Regency from 2017-2021. By using purposive sampling, 6 of 23 swallow nest entrepreneurs were chosen as informants. The data then were analyzed descriptively and qualitatively through data reduction, data presentation and conclusion. The results showed that swallow nests are classified into high quality, medium quality and low quality. The quality, which is classified based on the colour, cleanliness, shape and humidity, of the swallow's nest, determines the price of the swallow's nest. The marketing strategy of swallow's nest in Pelaihari District uses a community system for sales channels, face-to-face for sales transactions, market prices become the benchmark for sales, and there is no determination of product availability.